Point Deletion or Insertion in CmeR-Box, A2075G Substitution in 23S rRNA, and Presence of erm(B) Are Key Factors of Erythromycin Resistance in Campylobacter jejuni and Campylobacter coli Isolated From Central China - Cheng, Yiluo; Zhang, Wenting; Lu, Qin; Wen, Guoyuan; Zhao, Zhongzheng; Luo, Qingping; Shao, Huabin; Zhang, Tengfei (Frontiers in Microbiology, 2020)
Campylobacter jejuni and Campylobacter coli are major food-borne pathogens that cause bacterial gastroenteritis in humans, and poultry is considered as their most important reservoir. Macrolides, such as erythromycin, are the first-line choice for treatment of campylobacteriosis. In this study, of the 143 Campylobacter isolates recovered from poultry in central China during 2015–2017, 25.2% were erythromycin resistant. A2075G substitution in 23S ribosomal RNA (rRNA) and ribosomal methylase encoded by erm(B) were found in 4.2 and 4.9% isolates, respectively, and correlated with erythromycin resistance. The polymorphisms of CmeR-Box were also analyzed in our isolates. Among them, 9.1% isolates harbored a point deletion or insertion within the CmeR-Box, and we first showed that point deletion or insertion, but not substitution, in CmeR-Box led to high expression of cmeABC, which was significantly associated with erythromycin resistance (p < 0.05). These results suggest that point deletion or insertion in CmeR-Box, A2075G substitution in 23S rRNA, and presence of erm(B) are three main factors to erythromycin resistance in C. jejuni and C. coli.